Bilateral independent periodic discharges are associated with electrographic seizures and poor outcome: A case-control study. Issue 11 (November 2018) - Osman, Gamaleldin; Rahangdale, Rahul; Britton, Jeffrey W.; Gilmore, Emily J.; Haider, Hiba Arif; Hantus, Stephen; Herlopian, Aline; Hocker, Sara E.; Woo Lee, Jong; Legros, Benjamin; Mendoza, Michael; Punia, Vineet; et al.
Highlights: Bilateral independent periodic discharges (BIPDs) are caused by bilateral acute brain injury. BIPDs are associated with electrographic seizures, which occur in close to half of patients. BIPDs are associated with worse functional outcome. Abstract: Objective: To determine the clinical correlates bilateral independent periodic discharges (BIPDs) and their association with electrographic seizures and outcome. Methods: Retrospective case-control study of patients with BIPDs compared to patients without periodic discharges ("No PDs") and patients with lateralized periodic discharges ("LPDs"), matched for age, etiology and level of alertness. Results: We included 85 cases and 85 controls in each group. The most frequent etiologies of BIPDs were stroke, CNS infections, and anoxic brain injury. Acute bilateral cerebral injury was more common in the BIPDs group than in the No PDs and LPDs groups (70% vs. 37% vs. 35%). Electrographic seizures were more common with BIPDs than in the absence of PDs (45% vs. 8%), but not than with LPDs (52%). Mortality was higher in the BIPDs group (36%) than in the No PDs group (18%), with fewer patients with BIPDs achieving good outcome (moderate disability or better; 18% vs. 36%), but not than in the LPDs group (24% mortality, 26% good outcome). In multivariate analyses, BIPDs remained associated with mortality (OR: 3.0 [1.4–6.4]) and poor outcome (OR: 2.9 [1.4–6.2]). Conclusion: BIPDs are caused by bilateral acute brain injury and are associated with a high risk of electrographic seizures and of poor outcome. Significance: BIPDs are uncommon but their identification in critically ill patients has potential important implications, both in terms of clinical management and prognostication.